Transcriptional Regulation of Cardiac Development and Disease - Wagner, Nicole; Wagner, Kay-Dietrich (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This reprint contains original research and review articles describing recent advances in our understanding of the transcriptional regulation of cardiac development and disease mechanisms. All articles were originally published in the International Journal of Molecular Sciences (IJMS).